Meminimalisir Genangan Air dengan Metode Biopori - Darmawan, Moh. Faridl; Qomariyah, Siti Nur; Khakim, Arif Shofri; Hakiki, M Ainun; Ma’sum, Muhammad Haris; Khoir, Ila Nasichatul; Qodriyah, Khodijatul (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2025)
This community service was carried out to address water and environmental management issues in Kromong Village, Ngusikan District, Jombang Regency, which often faces flooding during the rainy season and drought in the dry season. This issue is exacerbated by the low level of public awareness regarding organic waste management and degradation of soil quality. The main focus of this service is to introduce biopori as a solution to increase water absorption, reduce puddles, and improve soil quality through organic waste management. The aim of this activity is to provide understanding to the community about the importance of the biopori technique and how its application can help overcome environmental problems faced by villages. The approach used is the service learning (SL) method, where the community is actively involved in socialization and training on the practice of making biopores. This research strategy includes several steps, such as problem identification, outreach, training, and monitoring the program's impact on the environment. The results of the service show success in increasing rainwater absorption, reducing the risk of flooding, and improving soil fertility through the decomposition of organic waste. In addition, there has been an increase in public awareness regarding the importance of sustainable environmental management. This program has also succeeded in reducing the amount of organic waste produced by households, while providing long-term benefits for groundwater security in the village. With positive results, it is hoped that this program can be replicated in other regions that face similar issues.